HUBUNGAN PROGRAM PARENTING YANG DIIKUTI OLEH ORANG TUA DI SEKOLAH DENGAN GAYA PENGASUHAN ORANG TUA DI TK IT BUNAYYA PEKANBARU - Nurafifah '; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This study aims to determine the relationship between parenting program followed by a parent at the school with the style of parenting in kindergarten IT Bunayya Pekanbaru. The method used in this study is a quantitative correlation method. The population in this study were all parents who follow the parenting program, amounting to 61 parents. Determination of the number of samples using probability sampling techniques as many as 38 parents. The data collection techniques used are questionnaire (questionnaire). Data were analyzed using analysis statistics person product moment correlation using SPSS Ver.20. The study hypothesis was a significant relationship between parenting program that is attended by the parents at the school with the style of parenting. It can be seen from the analysis of data obtained r = 0.345 and P = 0.034. Because p <0.05, it can be concluded that there is a significant relationship between the variables parenting program with parenting style variable So that means then Ho is rejected and Ha accepted, and proved significant. Determinant coefficient value generated amounted KP = r2 x 100% = 11.90%, it can be seen that a parenting program to give the effect of 11.90% against the style of parenting and the remaining 88.09% is determined by variables or other factors.Keyword: parenting program, style of parenting2HUBUNGAN PROGRAM PARENTING YANG DIIKUTI